Anne Boyd Rioux. El legado de Mujercitas. Construcción de un clásico en disputa. Ampersand: Buenos Aires, 2018. 363 pp. - Rossi, María Julia (Badebec, 2020)
Anne Boyd Rioux. El legado de Mujercitas. Construcción de un clásico en disputa. Ampersand: Buenos Aires, 2018. 363 pp.